Biochar application with reduced chemical fertilizers improves soil pore structure and rice productivity. (July 2022) - An, Ning; Zhang, Lei; Liu, Yaxian; Shen, Si; Li, Na; Wu, Zhengchao; Yang, Jinfeng; Han, Wei; Han, Xiaori
Abstract: Biochar is an efficient amendment to improve soil quality and crop productivity, but the potential of biochar as a substitute for chemical fertilizers is still unknown. Here we conducted a 6-year field experiment to investigate how partial substitution of biochar to NPK fertilizers affect soil quality and rice yield in the northeast of China. The experiment included three treatments: Control (B0: NPK fertilizers only: 240 kg N ha −1, 52 kg P ha −1, and 100 kg K ha −1 ); Low-input biochar (B1.5: 95% N, 89% P, 75% K + 1.5 t biochar ha −1 year −1 ); and High-input biochar (B3.0: 90% N, 78% P, 50% K + 3.0 t biochar ha −1 year −1 ). The amounts of NPK application in the biochar treatments were determined according to an equivalent method. We evaluated the soil pore structure characteristics via a CT technology, and investigated soil nutrients, plant biomass, root growth, and grain yields. The results showed that, after the 6-year application, the soil pore structure and rice productivity of B1.5 were significantly improved in compared to those of B0 and B3.0. B1.5 had similar soil available NPK contents, but 6.6% higher rice yield as compared to B0, because of increased root length density (33.2%) and aboveground biomass (10.2%). B1.5 also increased soil macroporosity (>100 μm) (141.4%), fraction dimension (8.4%), and pore connectivity (16.6%) in compared with those of B0. However, B3.0 showed the lowest rice yield due to lower soil available N content (19.2%), macroporosity (28.5%), fraction dimension (5.5%), and pore connectivity (85.3%) than B0. This study demonstrated that a moderate NPK fertilizer replacement by biochar could be an effective practice that improves soil quality, increases rice growth and yield, and reduces the input of chemical fertilizers for rice production. Graphical abstract: Image 1 Highlights: This study was based on a 6-year biochar application experiment in paddy soil. 1.5 t ha −1 of biochar maintained sufficient soil nutrients and improved pore structure. 1.5 t ha −1 of biochar increased rice productivity, but inverse in 3.0 t ha −1 .